18th Euromicro Conference on Real-Time Systems (ECRTS'06)
DOI: 10.1109/ecrts.2006.10
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Synchronization under Global EDF Scheduling on Multiprocessors

Abstract: We consider coordinating accesses to shared data structures in multiprocessor real-time systems scheduled under preemptive global EDF. To our knowledge, prior work on global EDF has focused only on systems of independent tasks. We take an initial step here towards a generic resource-sharing framework by considering simple shared objects, such as queues, stacks, and linked lists. In many applications, the predominate use of synchronization constructs is for sharing such simple objects. We analyze two synchroniz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 22 publications
(28 reference statements)
0
52
0
Order By: Relevance
“…A study performed by [Gai et al 2003] showed that MSRP typically outperforms MPCP when global critical sections are short and access to local resources dominates access to global resources. [Devi et al 2006], considered the problem of accessing mutually exclusive shared resources under global EDF scheduling. They suggested two simple approaches for short non-nested accesses to shared data structures: Spin-based queue locks [Mellor-Crummey and Scott 1991] and lock-free synchronisation.…”
Section: Partitioned Schedulingmentioning
confidence: 99%
“…A study performed by [Gai et al 2003] showed that MSRP typically outperforms MPCP when global critical sections are short and access to local resources dominates access to global resources. [Devi et al 2006], considered the problem of accessing mutually exclusive shared resources under global EDF scheduling. They suggested two simple approaches for short non-nested accesses to shared data structures: Spin-based queue locks [Mellor-Crummey and Scott 1991] and lock-free synchronisation.…”
Section: Partitioned Schedulingmentioning
confidence: 99%
“…For priority-assignment schemes that are known to offer good performance (deadline monotonic (DM) [10], RM-US(x) [I ] and DM-US(x) [12]). the combination of the resource-sharing protocol and the schedulability test should have the property that a large number of task sets can be given pre-run time guarantees ror deadline satisraetion; R9, Performance (as statcd by RS) should be particu larly good for the important special case that the duration for which tasks need shared resources is small; it has been shown that this special case applies to most applications in practice [6].…”
Section: Bjorn Anderssonmentioning
confidence: 99%
“…Let this system be scheduled on 'm processors using a global fixed-priority preemptive scheduler such that task Ti has higher base-priority than task Tj for all i < j. Then RTi is given as: given by Equations (6). (7).…”
Section: Therefore We Set (7)mentioning
confidence: 99%
“…Another shared resource arbitration algorithm is the Multiprocessor Stack Resource Protocol (MSRP) which is compared with MPCP in [12], showing that neither outperforms the other on the complete spectrum of system setups. In [13] Devi et al present a synchronization procedure specifically for multiprocessor scheduling under global EDF.…”
Section: Related Workmentioning
confidence: 99%